Pengaruh Layanan Informasi Terhadap Peningkatan Pengendalian Diri Siswa Kelas X SMAN 4 Pekanbaru T.P 2014/2015 - Enriati '; Tri Umari; Abu Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The title of this research is "The Effect of Information Services Improvement Self-Control Against Class X Sma Negeri 4 Pekanbaru " . The aim of this study. 1 ) To know the description of self-control ability of the student prior to the implementation of information services . 2 ) To know the process of implementation of information services in order to improve students' ability to 3 ) To know the description of self-control abilities of students after the implementation of information services . 4 ) To determine differences in the ability of self-control after the student prior to the implementation of information services . 5 ) To determine the effect of the implementation of information services to increase students' self-control . Data collection tools in the form of data self-control . Subjects were students of class X of SMAN 4 Pekanbaru , amounting to 352 people . Determination of the sample by using simple random sampling by means of a lottery and samples in this study were 106 people . Picture of self-control before being given information services 6 % of students with low self-control category , 94 % of students in the medium category , and 0 students in the Picture of self-control after the students are given information service found as many as 5 % in the high category , 95 % in the medium category , and 0 % in the low category . Based on the results of the calculation of the correlation coefficient between x1 and x2 is equal to 0.51 and the coefficient of determination r2 = 0.26 this means that the contribution of information services to increase self-control It can be seen that t count greater than ttable , ( 712.7 > 1.960 ) so that Ha is accepted . Means that there is influence of information services on self-control class X student of SMAN 4 Pekanbaru TP . 2014/2015 .Keywords : Information Services , Self-Control